Remuneración mínima vital y empleo urbano en el Perú: 2000-2016 - Mondragón Otero, Wilmer Bryam (2017)
The objective of this research is to analyze the influence of real minimum wage on the urban employment level in Peru during the years 2000 to 2016, for which the variables were evaluated individually, collecting information on employment and minimum wage of the databases of the Ministerio del Trabajo y Promoción del Empleo and of Banco Central de Reserva del Perú, respectively, both variables were monthly, and the linear regression method was used to detect a structural breakdown problem in the model. Include a Dummy variable, thus achieving a very significant improvement the model concluding that the real minimum wage has had a slightly positive influence on urban employment in Peru, it is presumed that this is caused because the real minimum wage was for Below the equilibrium wage in the labor market, this added to the increase of the productivity of the Peruvian economy basically by a high economic growth in the studied period.